2020
DOI: 10.1177/8755293020952442
|View full text |Cite
|
Sign up to set email alerts
|

Modeling spatial cross-correlation of multiple ground motion intensity measures (SAs, PGA, PGV, Ia, CAV, and significant durations) based on principal component and geostatistical analyses

Abstract: Ground motion intensity measures (IMs) were observed to be spatially correlated during past earthquakes. In this article, a new spatial cross-correlation model for a vector-IM, which consists of spectral acceleration (SA) ordinates at 17 periods and six non-SA IMs (e.g. peak ground velocity, Arias intensity, cumulative absolute velocity, and significant durations), is proposed using principal component analysis (PCA) and geostatistical analysis. A total of 3797 ground motion records are selected from the NGA-W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The range of periods of vibration is tailored to the dynamic properties of the building classes, as it covers the entire range of elastic to elongated periods at near collapse. The ANN models trained with this vector of IMs as input parameters achieved high levels efficiency (see Table 2), satisfy sufficiency and spatial and cross‐correlation of the IMs can be considered using existing models (e.g 70 …”
Section: Development Of An Ann Model For Vulnerability Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of periods of vibration is tailored to the dynamic properties of the building classes, as it covers the entire range of elastic to elongated periods at near collapse. The ANN models trained with this vector of IMs as input parameters achieved high levels efficiency (see Table 2), satisfy sufficiency and spatial and cross‐correlation of the IMs can be considered using existing models (e.g 70 …”
Section: Development Of An Ann Model For Vulnerability Assessmentmentioning
confidence: 99%
“…The ANN models trained with this vector of IMs as input parameters achieved high levels efficiency (see Table 2), satisfy sufficiency and spatial and cross-correlation of the IMs can be considered using existing models (e.g. 70 ). The additional computational effort related with the consideration of a wide spectrum of IMs in portfolio risk analysis is discussed in the final section.…”
Section: Nonlinear Dynamic Analyses and Training Of The Ann Modelsmentioning
confidence: 99%
“…24,26,27 Most previous studies have used recordings of well-recorded events assuming stationarity when developing spatial correlation models. [7][8][9][10][11]13,15,16,19,21,23,24,29 This means that the semivariogram, and thus the correlation between residuals at two different sites, do not depend on the site locations, but only on their separation distance. With this assumption, different station pairs with a given separation distance can be used to estimate the semivariogram, which is useful when there is a lack of station pairs with several simultaneous recordings.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial correlation of residuals of ground‐motion intensities has been extensively studied for the last 20 years 3–31 . In general, these studies combine several earthquakes for developing their models, although different authors have found a significantly large event‐to‐event variability, 12,23 even when exploring different events of the same seismic sequence 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation